2012
DOI: 10.1021/jf304465k
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Cellulose Crystallinity of Lignocelluloses Using Near-IR FT-Raman Spectroscopy and Comparison of the Raman and Segal-WAXS Methods

Abstract: Of the recently developed univariate and multivariate near-IR FT-Raman methods for estimating cellulose crystallinity, the former method was applied to a variety of lignocelluloses: softwoods, hardwoods, wood pulps, and agricultural residues/fibers. The effect of autofluorescence on the crystallinity estimation was minimized by solvent extraction or chemical treatment or both. Additionally, when the roles of lignin and hemicellulose in the Raman crystallinity assessment were investigated, it was found that syr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
87
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(94 citation statements)
references
References 28 publications
7
87
0
Order By: Relevance
“…Hemicelluloses do not show a peak at 380 cm À1 , whereas they can show broad peaks in the CH 2 bending vibration region. Thus, use of the 380 cm À1 Raman peak intensity is advantageous for CI calculation [48]. Figure 1c displays the IR spectra of the same samples.…”
Section: Correlation Of "Apparent" Crystallinity Estimated From Xrd mentioning
confidence: 99%
“…Hemicelluloses do not show a peak at 380 cm À1 , whereas they can show broad peaks in the CH 2 bending vibration region. Thus, use of the 380 cm À1 Raman peak intensity is advantageous for CI calculation [48]. Figure 1c displays the IR spectra of the same samples.…”
Section: Correlation Of "Apparent" Crystallinity Estimated From Xrd mentioning
confidence: 99%
“…In addition to XRD, crystallinity in cellulose samples can be determined with many other methods, such as Raman spectroscopy (Schenzel et al 2005;Agarwal et al 2013;Kim et al 2013), infrared spectroscopy (Kljun et al 2011;Chen et al 2013;Kim et al 2013), differential scanning calorimetry (Gupta et al 2013;Kim and Kee 2014), sum frequency generation vibration spectroscopy (Barnette et al 2012;Kim et al 2013), and solid state nuclear magnetic resonance (NMR) (Davies et al 2002;Liitiä et al 2003;Park et al 2009;Kim et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Cellulose crystallinity of woods can be determined using a number of analytical techniques, such as X-ray diffraction (Andersson et al 2003;Leppänen et al 2009), NMR (Newman and Hemmingson 1990;Newman 1999), Raman (Agarwal et al 2013a), and sum frequency generation vibrational spectroscopy (Barnette et al 2012). It is clear from the literature that various methods provide values of crystallinity that are different (Park et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, using the univariate Raman method, the crystallinity of woods and other lignocelluloses was estimated (Agarwal et al 2013a) and it was reported that with proper corrections for the contributions of syringyl lignin and hemicelluloses, the method generated accurate values of wood crystallinity. In this context, it is important to note that compared to Segal-WAXS (Segal et al 1959), the Raman estimate is usually lower because it is correlated with the 21-Segal-WAXS, where 21 designates the 2h where amorphous contribution was measured (and subtracted) (Agarwal et al 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation